(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SUMARIO: 1. Planteamiento de la cuestión - 2. El catolicismo-nacionalista de ciertos símbolos evocadores de lo religioso - 3. ¿Los símbolos religioso-franquistas pueden permanecer en ámbitos públicos? - 3.1. Supuesto en que el símbolo religioso no ha de tenerse por vestigio franquista - 3.2. Supuesto en que el símbolo ha de tenerse por vestigio franquista - 4. Consideraciones conclusivas. ABSTRACT: The present article argues if, under the interpretation and application of the so-called Historical Memory Law, Franco’s regimen would have set the basis to divest itself as part of the Catholicism that characterized it, in terms of having some symbols that originally would have been considered religious and now they cease to be so, historically and inevitably, at least in a retrospective point of view. In other terms, for the current time to impose a type of victim, although final of Franco’s regimen in the manner of, as a paradox, for some religious symbols to cease to be, without any other possibility for its political use as far as ‘semel francoist semper francoist’ can no longer recover that religious value. This matter, whether it refers, principally to the “Cruces de los Caídos” it can also be argued for it to attain the crucifix and the Virgin Mary located in public places by order of the dictatorial regimen.